ANALISIS IMPLEMENTASI METODE ACTIVITY BASED COSTING UNTUK PERUSAHAAN INDUSTRIAL - SAFRI SAFRI (JURNAL TEKNIK INDUSTRI, 2018)
Traditionally, charging for costs not directly done using the basic loading thoroughly. This will cause many problems because the products can not reflect the actual cost is absorbed to produce the products. As a result will appear under the product costing and product costing over. Activity Based Costing systems can provide costing information better and can help management manage the company efficiently and gain a better understanding on competitive advantages , strengths , and weaknesses of the company. Keywords: Activity Based Costing